2017
DOI: 10.1007/s00285-017-1191-9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-patch and multi-group epidemic models: a new framework

Abstract: We develop a multi-patch and multi-group model that captures the dynamics of an infectious disease when the host is structured into an arbitrary number of groups and interacts into an arbitrary number of patches where the infection takes place. In this framework, we model host mobility that depends on its epidemiological status, by a Lagrangian approach. This framework is applied to a general SEIRS model and the basic reproduction number [Formula: see text] is derived. The effects of heterogeneity in groups, p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
41
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 44 publications
(75 reference statements)
1
41
0
3
Order By: Relevance
“…where denotes the Hadamard division. Relations (4) and (5) imply the attractivity of the DFE. Moreover, by [16,43], the DFE is locally asymptotically stable whenever R 2 0 (m, n, p) < 1.…”
Section: The Disease Free Equilibriummentioning
confidence: 99%
“…where denotes the Hadamard division. Relations (4) and (5) imply the attractivity of the DFE. Moreover, by [16,43], the DFE is locally asymptotically stable whenever R 2 0 (m, n, p) < 1.…”
Section: The Disease Free Equilibriummentioning
confidence: 99%
“…We revisit this framework in possibly the simplest general setting that of a susceptible-infected-susceptible (SIS) epidemic multi-group model. We collect some of the mathematical formulae and results in the context of this general SIS multi-group model as reported in the literature [4,6,7,11]. We proceed to identify basic reproduction numbers R 0 as a function of the associated multi-patch residence-time matrix P (p i,j : i, j = 1, 2, 3 .…”
mentioning
confidence: 99%
“…We have used simulations to generate insights on the impact that the residence matrix P has on infection levels within each patch. Model results [4,6,7,11] show that the infection risk vector, which characterizes environments by risk to a pre-specified disease (measured by B), and the residence-time matrix P both play an important role in determining, for example, whether or not endemicity is reached at the patch level. Further, it is shown that the right combinations of environmental risks (B) and mobility behavior (P) are capable of promoting or suppressing infection within particular patches.…”
mentioning
confidence: 99%
See 2 more Smart Citations